(untitled) (Medico Legal Update, 2020)
“Assessment of knowledge on Disaster preparedness among Adults’’. The objectives of this study are to assess the level of knowledge on disaster preparedness among adults and associate the knowledge on disaster preparedness among adults with selected demographic variables. The sampling technique used was simple random sampling technique with the samples of 100 adults. The study assessed the knowledge on disaster preparedness among adults. The data collection tool was validated by nursing experts. The collected data was tabulated and analyzed. That based on the age of adults 69(69%) of adults were in between 20-40 years, 26(26%) were in between 41-59 years, 5(5%) were above 60 years. According to the sex distribution 52(52%) were male and 48(48%) were female. According to the educational status 72(72%) were studied up to primary and middle school, 23(23%) were studied upto secondary and higher secondary education school and 5(5%) were under graduate. Regarding the type of disaster 68 were experienced flood, 72 were experienced cyclone, 20 were experienced earthquake and 1 were experienced draught . Regarding the sources of knowledge subjects gained knowledge from newspaper 16(16.4%), from television 82(84.4%), from phone 3(3.09%), from Panchayat 1(1.03%) and from pamphlet 1(1.03%). Regarding previous disaster status 42(42%) were experienced disaster once, 36(36%) were experienced disaster twice and 22(22%) were experienced disaster more than thrice . To create the awareness among public and to reduce the Impact of disaster.